Magnetically retrievable 2-(2-Pyridyl)benzimidazole-Cu(I) on SBA-15@Fe3O4 for sodium Azide-Induced amination of Aryl halides - Zoleikha Abbasi; Yagoub Mansoori; Somayeh Fekri; Yuksel Akinay; Tayfun Çetin (Scientific Reports)
Abstract This study reports the synthesis and thorough characterization of a novel copper catalyst immobilized on magnetic mesoporous silica (Fe3O4@SBA-15). The catalyst preparation involved stepwise functionalization of Fe3O4@SBA-15 through sequential treatment with (3-aminopropyl)triethoxysilane (APTES), trichlorotriazine, and 2-(2-pyridyl)benzimidazole, resulting in Fe3O4@SBA-bis(PBI). Subsequent coordination with CuI in acetonitrile produced the final catalyst complex, Fe3O4@SBA-bis(PBI)-Cu. Extensive characterization was performed using standard spectroscopic techniques. The copper content of the catalyst was determined by atomic absorption spectroscopy to be 0.866 mmol g−1 (5.5 wt%). Catalytic performance evaluation demonstrated that Fe3O4@SBA-bis(PBI)-Cu effectively catalyzes the conversion of iodo-, bromo-, and chloroarenes to their respective anilines, using NaN3 as the nitrogen source. Notably, the catalyst exhibited excellent recyclability, maintaining catalytic activity over six successive cycles with minimal deactivation, highlighting its robustness and suitability for sustainable catalytic applications in organic synthesis. The low metal leaching (0.4%) shows that the copper is firmly bound to the ligand, and the reaction was mainly carried out by a heterogeneous catalyst.